2010
DOI: 10.1093/humrep/deq113
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and meiotic segregation in ejaculated sperm from Robertsonian translocation carrier patients

Abstract: These results show a predominant proportion of balanced and normal gametes and higher numbers of spermatozoa showing apoptosis and immaturity features in oligoasthenozoospermic Robertsonian translocation carriers than in fertile donors. This suggests defects in spermatogenesis and especially spermiogenesis of these infertile patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 48 publications
6
37
0
Order By: Relevance
“…Eaker et al [9] showed increased apoptosis markers and asynapsis in unbalanced sperm in the mouse. Increased apoptosis markers were shown in humans as well [6,7]. The nature of the rearrangement, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Eaker et al [9] showed increased apoptosis markers and asynapsis in unbalanced sperm in the mouse. Increased apoptosis markers were shown in humans as well [6,7]. The nature of the rearrangement, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that this association between chromosomal imbalance and DNA fragmentation has only been shown in ten patients so far (four by Perrin et al in [18], and six in the present study). However, since the association between DNA fragmentation, apoptosis markers, and chromosomal rearrangements has been evidenced in multiple studies [6,7,17], it is possible than in most if not all of the patients analyzed in those studies, DNA fragmentation is more often found among unbalanced spermatozoa. Therefore, it is likely that our population of six patients is representative of the chromosomal events in sperm from translocations carriers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations